Displaying lecturers room and information based on virtual reality / Abdul Hasib Sadiqin Adam Shukri - Adam Shukri, Abdul Hasib Sadiqin (2010)
The purpose of the study is to prove that a 3D technology and Virtual Reality are needed in displaying lecturer's room and information on the faculty website. Another aim was to find out about the effectiveness of Lecturers Room and Information using 3Denvironment. Questionnaires were distributed to 20 students' of the faculty of computer and mathematical sciences and non probability sampling was carried out. One conclusion was that, the use of 3D technology and Virtual Reality on the website is needed.